2007
DOI: 10.1177/089686080702700615
|View full text |Cite
|
Sign up to set email alerts
|

Intraperitoneal Calcitriol in Infants on Peritoneal Dialysis

Abstract: Background Calcitriol has long been used as the main therapy in renal osteodystrophy, but the efficacy of the oral route is not always as high as expected. Objective To asses the safety and efficacy of intraperitoneal calcitriol in infants undergoing peritoneal dialysis (PD). Patients and Methods PD patients on oral calcitriol therapy, with serum parathyroid hormone (PTH) >1000 pg/mL during the previous 3 months of treatment, were switched to intraperitoneal calcitriol therapy, 1 μg twice per week. Dose was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The IP group demonstrated higher calcium levels, a significant reduction in PTH, and lower serum phosphorus levels than the oral group (2). The efficacy of IP calcitriol has also been confirmed in infants on PD (8). None of these studies reported any major side effects related to IP calcitriol administration.…”
Section: Discussionmentioning
confidence: 92%
“…The IP group demonstrated higher calcium levels, a significant reduction in PTH, and lower serum phosphorus levels than the oral group (2). The efficacy of IP calcitriol has also been confirmed in infants on PD (8). None of these studies reported any major side effects related to IP calcitriol administration.…”
Section: Discussionmentioning
confidence: 92%
“…In a prospective uncontrolled trial, six children not responding to oral calcitriol treatment for >12 months were given intraperitoneal calcitriol and showed a significant decrease in PTH levels after 9 months, but also significantly more episodes of hypercalcaemia and hyperphosphataemia on intraperitoneal treatment [53]. Calcitriol is no longer licensed for intraperitoneal use.…”
Section: Strength Of Recommendation: 2 Level Of Evidence: Bmentioning
confidence: 99%
“…In this issue of Peritoneal Dialysis International , Cano et al report the use of the intravenous form of calcitriol (Calcijex, 1 μg/mL; Abbott Laboratories, Abbott Park, Illinois, USA) given intraperitoneally to a cohort of infants undergoing PD with persistent 2°HPT despite conventional therapy with oral doses of calcitriol (3). Patients entering the study had serum parathyroid hormone (PTH) levels >1000 pg/mL despite treatment with oral calcitriol therapy (0.01 – 0.05 μg/kg/day) and calcium-based binders for at least 1 year.…”
mentioning
confidence: 99%